PSI-16 Investigation of Jute to Stimulate Sow Nesting Behavior in Farrowing Crates. (30th November 2020) - Markland, Mary L; Gaskill, Brianna N; Johnson, Jay S; Lay, Donald C
Abstract: Domesticated sows are highly motivated to perform nesting behavior prior to farrowing. However, due to the potential for clogging slurry systems, large amounts of nesting material are not practical to use in most production systems. Therefore, the study objective was to assess an alternative nesting material provided prior to farrowing on sow welfare and reproductive outcomes. We hypothesized that the provision of jute nesting material would decrease sow stress and improve reproductive outcomes. Twenty-one sows were randomly assigned to 1 of 2 treatments: farrowing crate with jute nesting material (n = 11; 40.64 x 21.59 cm) or farrowing crate without nesting material (n=10). Three overlapping jute pieces were attached to the front of the crate to prevent substrate from falling through the slatted floors and disrupting the slurry system. Sows had access to the jute from the time they were moved into the crates (112.4 ± 0.5 d of gestation) until the end of farrowing. Saliva samples were collected, as a non-invasive way to measure cortisol and immunoglobulin A (IgA) to assess stress, on d -1, 0, 1, and 2 relative to farrowing, and a final sample was collected at weaning. Video was continuously coded for observations of jute-oriented interactions. Data were analyzed as GLM using JMP. In the 12 h prior to farrowing, sows spent an average of 30.02 ± 33.12 min interacting with the jute. Although the sows appear to interact with the material, farrowing duration, number of stillborns, IgA, and cortisol did not differ between treatments (P > 0.05). In summary, the treatment was likely not robust enough to satiate the sows' nest-building needs. Therefore, alternative nesting materials that provide a better outlet for sow behavior, while avoiding negative effects on the slurry system, or ways to present that material should be evaluated to improve sow welfare.